Bioinspired bubble design for particle generation. - Gunduz, O; Ahmad, Z; Stride, E; Tamerler, C; Edirisinghe, M (2012)
In this study, we devise a method to generate homogeneous particles from a bubble suspension, with the capability to control loading and the structure of bubbles. Ideally, a process such as this would occur at the interface between daughter bubble formation (instant) and gaseous diffusion (gradual). Interestingly, the budding mechanism in micro-organisms is one that demonstrates features of the desired phenomena (although at a much slower rate), as viruses can eject and evolve structures from their membranes. With these natural concepts, a bubble's surface can also be made to serve as a platform for particle generation, which transfers significant elements from the initial bubble coating to the newly generated structures. Here, we illustrate this by preparing coated bubbles (approx. 150 µm in diameter) using a hydrophobic polymer, which may be comparable to naturally occurring bubble coatings (e.g. organic matter forming part of bubble coatings in the sea), and dye (which can demonstrate entrapment of smaller quantities of a desired moiety) and then observe particle generation (approx. 500 nm). The process, which may be driven by a polymerosome-forming mechanism, also illustrates how additional uniform sub-micrometre-scale structures may form from a bubble's surface, which may have also previously been attributed to gas diffusion. In addition, such methods of particle formation from a bubble structure, the incorporation of chemical or biological media via an in situ process and subsequent release technologies have several areas of interest across the broad scientific community.